Persepsi Siswa Kelas XII SMA Istiqlal Deli Tua Mengenai Peran Keluarga Dalam Pembentukan Karakter - Brasa, Ayu Astuti; Mavianti, Mavianti (Journal of Sustainable Education, 2025)
This study aims to describe the perception of grade XII students of SMA Istiqlal Deli Tua regarding the role of family in character formation. The research uses a qualitative approach with a case study method. The research subjects consisted of three students who were selected purposively based on the representation of family backgrounds and involvement in character activities in the school. The data collection technique was carried out through semi-structured interviews and documentation, while the data analysis followed the stages of reduction, presentation, and conclusion drawn. The results of the study show that students view family as the main factor in character formation, especially in the aspects of discipline, responsibility, empathy, and respect. Parental examples, open communication, habituation of positive values, and emotional support at home are the dominant factors that shape students' character. In contrast, students who come from families with permissive parenting tend to have difficulty maintaining character values at school. This perception confirms that the success of character education in schools is highly dependent on alignment with the values instilled in the family. Therefore, intensive cooperation between schools and families is needed to create an environment conducive to strengthening students' character.